2019
DOI: 10.3390/cells8040303
|View full text |Cite
|
Sign up to set email alerts
|

Combined Targeted Omic and Functional Assays Identify Phospholipases A2 that Regulate Docking/Priming in Calcium-Triggered Exocytosis

Abstract: The fundamental molecular mechanism underlying the membrane merger steps of regulated exocytosis is highly conserved across cell types. Although involvement of Phospholipase A2 (PLA2) in regulated exocytosis has long been suggested, its function or that of its metabolites—a lyso-phospholipid and a free fatty acid—remain somewhat speculative. Here, using a combined bioinformatics and top-down discovery proteomics approach, coupled with lipidomic analyses, PLA2 were found to be associated with release-ready cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 113 publications
(338 reference statements)
0
6
0
Order By: Relevance
“…This Rab family 1 motif is largely conserved (>50%) among the Rab GTPases and across different species (Table 2), and this effector domain peptide has been previously shown to interfere with the formation of the fertilization envelope in urchin oocytes [47]. An addition of exogenous RAB peptide inhibited the extent of fusion by~63% in the modified settle assay, compared to~46% in the standard assay; this strongly indicates an effect on upstream stages of CV tethering/docking/priming [1][2][3]6,8,30,39]. With the addition of the RAB effector domain, there was no effect on Ca 2+ -sensitivity; however, after pretreatment with IA, treatment with the RAB peptide resulted in a decrease in Ca 2+ -sensitivity, mitigating the potentiation effect of IA.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This Rab family 1 motif is largely conserved (>50%) among the Rab GTPases and across different species (Table 2), and this effector domain peptide has been previously shown to interfere with the formation of the fertilization envelope in urchin oocytes [47]. An addition of exogenous RAB peptide inhibited the extent of fusion by~63% in the modified settle assay, compared to~46% in the standard assay; this strongly indicates an effect on upstream stages of CV tethering/docking/priming [1][2][3]6,8,30,39]. With the addition of the RAB effector domain, there was no effect on Ca 2+ -sensitivity; however, after pretreatment with IA, treatment with the RAB peptide resulted in a decrease in Ca 2+ -sensitivity, mitigating the potentiation effect of IA.…”
Section: Discussionmentioning
confidence: 93%
“…Along with cholesterol-and sphingomyelin-enriched membrane domains [8][9][10][11]45,46], other lipid species, such as phosphoinositides, participate in the organization of the exocytotic machinery at release sites [4]. The generation of phospholipid metabolites from phospholipase D [3] and phospholipase A [2] can also modulate the efficiency of exocytosis via roles in upstream stages, such as docking/priming. Here, we have identified two labeled enzymes involved in lipid metabolism, long-chain-fatty-acid-CoA ligase 1 and long-chain specific acyl-CoA dehydrogenase, which may have roles in regulating local fatty acid metabolism in secretory vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an independent follow-up study showed that the cleavage product was formed by degradation of the first eight N-terminal residues and was attributable to the inappropriate storage of samples (i.e., at −20 °C rather than −80 °C; [ 186 ]). Most importantly, the use of broad-spectrum inhibitor cocktails (e.g., containing protease, kinase, and phosphatase inhibitors) is essential to achieve high-confidence analyses that reflect the native proteome at the time of sampling [ 104 , 135 , 187 ]. Proteolysis in vitro is a nonspecific alteration of the native proteome being analysed [ 188 ] and the addition of broad-spectrum protease inhibitors is thus essential to block the degradation of proteoforms [ 189 ].…”
Section: Other Factors Affecting Proteomic Analysesmentioning
confidence: 99%